Determinants of neighborhood satisfaction among local residents and international students: A case study in famagusta, north cyprus - Oktay, Derya; Rüstemli, Ahmet; W.Marans, Robert (My University, 2012)
This study examines relationships between neighborhood satisfaction and selected measures of perceived neighborhood quality among local residents and international students residing in the rapidly growing Eastern Mediterranean city of Famagusta, North Cyprus.We measured residents' sense of the neighborhood as home (i.e., neighborhood attachment) and perceptions of seven neighborhood attributes - attractiveness, appropriateness as a place to live, availability of things to do, accessibility, environmental maintenance, traffic density, and noise level - by interviewing a probability sample of 302 local residents and 96 international students from different households using a standardized questionnaire.The results of the analysis indicated significant differences among the local people and international students with regard to attributes contributing to neighborhood satisfaction.Although both groups were satisfied with their neighborhoods, regression analyses demonstrated that appropriateness of the neighborhood as a place to live and sense of the neighborhood as home were most important for local residents, while neighborhood attractiveness and accessibility were most important for students. © 2012, Locke Science Publishing Company, Inc.Chicago, IL, USA.
Keywords: accessibility; environmental education; neighborhood; probability; regression; residential development; student; traffic congestion; Cyprus; Famagusta [Cyprus]; Famagusta [Famagusta (DST)]